A wolf in sheep's clothing: how Monitor is using licensing powers to reduce hospital and community services in England under the guise of continuity. (7th October 2014) - Roderick, Peter; Pollock, Allyson M
Abstract : Peter Roderick and Allyson M Pollock argue that the licence conditions imposed by Monitor on NHS foundation trusts will lead to a reduction in hospital services, and they question the legality of Monitor's approach